Encouraging rainforest preservation by smallholders: An ex-ante policy evaluation - Arieska Wening Sarwosri; Johannes Wegmann; Oliver Mußhoff (GOEDOC, Dokumenten- und Publikationsserver der Georg-August-Universität, 2018)
Deforestation is one of many factors that hinder smallholder farmers' participation in sustainable palm oil (SPO) certification. Thus, policies that enhance the appetite for rainforest preservation might be helpful to increase the participation rate in certification schemes. Our study aims to investigate ex-ante the effects of several promising policies on mitigating deforestation. To do so, we used an incentivized experiment which creates a conflict of short-term individual interests and long-term collective interests regarding deforestation. We examined the effects of three policies: price premiums, provision of environmental information, and contributor recognition. Our research took place in Jambi Province, Sumatra, and involved 636 smallholders. We found that price premiums and the provision of context-specific environmental information reduce rainforest transformation. However, there is an absence of significant effects for contributor recognition. Our results also can be used to estimate the participation of smallholders in more sustainable farming practices within the scheme of SPO certification.
urn:nbn:de:gbv:7-webdoc-3984-3
Keywords: 330; Deforestation; Ex-ante policy evaluation; Framed field experiment; Palm oil certification; Social dilemma experiment